A biomimetic photoelectrocatalyst of Co–porphyrin combined with a g-C3N4 nanosheet based on π–π supramolecular interaction for high-efficiency CO2 reduction in water medium. Issue 24 (28th November 2017) - Liu, Jibo; Shi, Huijie; Shen, Qi; Guo, Chenyan; Zhao, Guohua
Abstract : Aiming at high-efficiency biomimetic CO2 reduction, a photoelectrocatalyst with excellent CO2 catalytic activity was designed and prepared by self-assembly immobilizing CoTPP onto g-C3 N4 based on π–π interaction. Abstract : Aiming at high-efficiency biomimetic CO2 photoelectrochemical conversion, a photoelectrocatalyst with excellent CO2 catalytic activity was designed and prepared by immobilizing CoTPP (cobalt meso -tetraphenylporphyrin) onto g-C3 N4 conveniently via self-assembly based on π–π supramolecular interaction. The quasi 3-D structure of CoTPP showed a suitable hole with a size of 3.8 Å × 9.6 Å which favoured CO2 adsorption. The pores formed by the π–π stacking of CoTPP and g-C3 N4 also provided additional space for CO2 adsorption, which was confirmed by the appearance of a desorption peak at 250 °C in the temperature programmed desorption measurement for CoTPP/g-C3 N4 . As a normal efficient homogeneous catalyst in organic media, CoTPP commendably maintained outstanding CO2 photoelectrocatalytic activity in heterogeneous aqueous solution, even at a low overpotential of −0.6 V ( vs. normal hydrogen electrode, NHE). Under 8 h PEC CO2 reduction, formic acid generation on CoTPP/g-C3 N4 reached 154.4 μmol with a TON of 137 and high selectivity of nearly 100% in liquid products. The formation of CoTPP–COO − and CoTPP–COOH intermediates by the Co(ii ) active site and CO2 was investigated by in situ UV-vis and Raman spectra. Moreover, an isotopic labelling experiment indicated that water supplied abundant protons for the production of formic acid.